Strategi Peningkatan Kesejahteraan Sosial Desa Sukawening untuk Ketahanan Ekonomi Keluarga dalam Mewujudkan Desa Inovasi Perikanan - Ananda Frestiana; Canta Bayu Laksana; Istiqlaliyah Muflihkati; Muhammad Obdal Amfa; Ramadhani Irdiansyah; Rizky Darmawan (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Village development is the empowerment of human development, development based on local resources and of course institutional development. Sukawening Village is one of the villages in Dramaga District, Bogor Regency. The fishery potential in Sukawening village is quite good with irrigation that has good air fertility for fish and also some marine commodities. The purpose of the IPB Goes to Field Program is to increase the economic resilience of the Sukawening village community in realizing fisheries innovation villages. The method used in data collection is the experimental experimental method. Several forms of design that can be used in experimental research. This questionnaire, the researcher uses a pre-experimental design questionnaire by not including the control group, but there are still variables that also affect the dependent variable with the type of post test one group pre-test design. The results of this service program state that the community can understand and practice the manufacture and use of simple technology using budikdamber technology, the community gets knowledge in Sukawening Village about the advantages of Budikdamber for food security and fisheries innovation village readiness strategies. Keywords: budikdamber, community service, fishery